Кiральна асиметрiя в релятивiстськiй матерiї у зовнiшньому магнiтному полi - Gorbar, E. V. (Publishing house "Academperiodika", 2019)
In this mini review, we consider chiral asymmetry in the normal ground state of magnetized relativistic matter in the NJL model with local four-fermion interaction and QED. It is shown that the chiral shift parameter associated with the relative shift of the longitudinal momenta (along the direction of the magnetic field) in the dispersion relations for opposite chirality fermions is dynamically generated in the normal ground state. This contribution affects fermions in all Fermi levels, including those around the Fermi surface, and contributes to the non-dissipative axial current taking place in relativistic matter in a magnetic field. The chiral asymmetry of the normal ground state in QED matter in a magnetic field is characterized by an additional chiral structure. It formally looks like that of the chiral chemical potential, but is an odd function of the longitudinal component of momentum along the magnetic field. The origin of this parity-even chiral structure is directly connected with the long-range character of the QED interaction. The leading radiative corrections to the chiral separation effect in QED are calculated, and the form of the Fermi surface in the weak magnetic field is determined.